Enhanced Safety and Efficacy of O‐Arm Navigation Over C‐Arm Guidance in Percutaneous Kyphoplasty for Patients With Osteoporotic Vertebral Compression Fractures and Spinal Deformity: A Comparative Study - Zhong‐Wei Ji; Min‐Jie Shen; Jia‐Jia Sun; Jia‐Le Wang; Yong‐Kang Deng; Yao Zhang; Xie‐Xing Wu; Kang‐Wu Chen; Hai‐Qing Mao (Orthopaedic Surgery)
ABSTRACT Objective Although percutaneous kyphoplasty (PKP) under C‐arm guidance is an effective treatment for osteoporotic vertebral compression fractures (OVCF), obtaining high‐definition images in patients with OVCF and spinal deformities can be challenging or insufficient using traditional C‐arm guidance, prompting our institution to adopt the O‐arm navigation system—which offers comprehensive 3D imaging and precise navigation—and this study compares its safety and efficacy with conventional C‐arm‐assisted PKP. Methods This was a retrospective study. From February 2019 to February 2022, we enrolled 28 patients with OVCF (44 vertebrae) with spinal deformity treated with O‐arm navigation‐assisted PKP and 30 patients with OVCF (42 vertebrae) with spinal deformity treated with C‐arm‐guided PKP. We recorded puncture times, single‐segment operation time, number of cases with bone cement leakage, and length of stay. The visual analog scales (VASs), Oswestry disability indexes (ODIs), recovery of Cobbs angle, and vertebral height were used to assess treatment effect before the operation, on the first day postoperation, the first month postoperation, and at the final follow‐up. The chi‐squared test was utilized for comparing discrete variables, an independent samples t‐test was used for continuous variables, and Pearson's chi‐squared test and Fisher's exact test were applied for categorical data. Results Demographic features were comparable between the groups. The O‐arm navigation group showed a significant reduction in puncture adjustment per vertebrae, single‐segment operation time, and the rate of trocar needle malposition compared to the C‐arm guidance group. The rate of cement leakage was decreased in the O‐arm‐guided PKP group, and other complications did not differ between the two groups. Intragroup comparisons revealed significant improvements in VAS scores and ODI on the first day, first month, and final follow‐up after the operation (p < 0.05). The VAS score was significantly lower in the O‐arm navigation‐assisted PKP group than in the C‐arm‐guided PKP group on the first day postoperatively (p = 0.049). However, no significant differences in VAS scores were observed between the groups at the first month postoperatively or at the final follow‐up. In each follow‐up period, there was no significant difference in ODI, Cobb angle, and the percent of anterior vertebral height (AVH %) between the groups. Conclusion O‐arm navigation‐assisted PKP demonstrates better clinical safety and efficacy than C‐arm‐guided PKP, marking it as a minimally invasive, safe, and effective procedure for treating patients with OVCF with spinal deformity.